1998
DOI: 10.1136/jcp.51.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Antimony in blood and urine of infants.

Abstract: Aim-To establish a reference range for antimony in the serum and urine of infants in the first year of life. Methods-100 infants were selected randomly from the population. Each infant had a single blood and urine sample taken. Antimony was assayed using inductively coupled plasma mass spectrometry. Results-The reference range for antimony in the serum of infants in the first year of life was established as 0.09-0.25 µg/l. The upper 95% centile for urinary antimony, corrected for creatinine, in the same popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
2
8
1
1
Order By: Relevance
“…Earlier measurements in general populations or compiled reference ranges (Hamilton et al, 1994) have reported values slightly higher than those in this Report, which may be due to methodologic, population, or exposure differences. Levels of urinary antimony in infants appeared to be similar to those reported by CDC (2005) for young children (Cullen et al, 1998;Dezateux et al, 1997). Urinary antimony was not associated with locally elevated soil levels in a study of more than 200 German residents (Gebel et al, 1998).…”
Section: Biomonitoring Informationsupporting
confidence: 60%
“…Earlier measurements in general populations or compiled reference ranges (Hamilton et al, 1994) have reported values slightly higher than those in this Report, which may be due to methodologic, population, or exposure differences. Levels of urinary antimony in infants appeared to be similar to those reported by CDC (2005) for young children (Cullen et al, 1998;Dezateux et al, 1997). Urinary antimony was not associated with locally elevated soil levels in a study of more than 200 German residents (Gebel et al, 1998).…”
Section: Biomonitoring Informationsupporting
confidence: 60%
“…These infants formed part of a study, the details of which have been outlined in an earlier report 14. It was noted that five (17%) of the 30 SIDS values were higher than the upper limit of the control values (0.3 μg/litre after excluding the outlier result) and that 15 (50%) of the SIDS values and one (17%) of the six control values were above the upper limit of the previously established reference range for this random population (0.25 μg/litre).…”
Section: Resultsmentioning
confidence: 99%
“…Infants in the 1st year of life were found to have a urinary antimony concentration corrected for creatinine (Cr) of less than 2.6 ng/mg Cr 14. In our study, urine samples were available from only eight infants dying from SIDS and four control infants.…”
Section: Resultsmentioning
confidence: 99%
“…Careful morphologists have an impressive ability correctly to predict presence of a rearranged BCR/ABL, even in those rare cases of Ph negative CGL. 5 After further emphasis of the crucial role of morphological assessment, 6 the diagnostic criteria for these three entities were incorporated into an internationally accepted classification. 7 A prerequisite for morphological diagnosis is that the blood film is conscientiously examined.…”
Section: Do We Critically Appraise the Evidence?mentioning
confidence: 99%